THE INFLUENCE OF DIGITAL MARKETING, BRAND IMAGE AND PRODUCT QUALITY ON PRODUCT PURCHASING DECISIONS AT THE KING MS GLOW SHOP IN THE CITY OF BENGKULU - Ghaefira Nur Fatimah; Islamuddin (International Journal of Accounting, Finance and Business, 2023)
This study aims to explain the influence simultaneously (together) or partially between the influence of Digital marketing, brand image and product quality on purchasing decisions. This study uses a quantitative approach with survey research methods to obtain primary data. The samples of this study were 110 consumers respondents of King MS Glow Bengkulu City by taking the entire population and serving as samples. The data collection method used is the distribution of questionnaires. The data analysis technique in this study used multiple regression analysis which was previously carried out with Validity, Reliability, Classical Assumption Tests (normality test, multicollinearity test, heteroscedasticity test) then tested the hypothesis through T test, F test and coefficient of determination test. The results of this study indicate that partially Digital Marketing have a positive effect, brand image and product quality have a positive and significant effect on purchasing decisions for King MS Glow Bengkulu. Meanwhile, simultaneously the results of this study also show that social media marketing, brand image and product quality have a positive and significant effect on purchasing decisions for King MS Glow Bengkulu products.